Using project method for the purpose of educating future music teachers - Rolinska, Helena H. (Linguistics and Culture Review, 2021)
The article discusses the specifics of applying project method to the educational process. The analysis of scientific materials that concern themselves with applying project method is carried out, their main principles are highlighted, and a project model is proposed. Studies conducted in the field of project method were used as materials for this work. During the research, methods of analysis, synthesis, comparison, deduction and induction were used. The research hypothesis is based on the assumption that applying project method to the training process of future music teachers will help students with improving their professional competencies, and increase the motivation to learn. The study proved that applying project method to the training process of educating future music teachers allows for better pedagogical training, motivating students to work more actively, display creativity, and identity. The project method allows students to receive skills of independent and group work, short and long-term planning, and self-assessment. General positive characteristics of applying project method to the training process of educating future music teachers proves the need to adopt this method in higher education institutions. This paper is intended for teachers and students who will implement creative projects while receiving music education.